The integration of glutathione homeostasis and redox signaling - Meyer, Andreas (Journal of plant physiology, 2008)
Summary Formation of reactive oxygen species (ROS) is a common feature of abiotic and biotic stress reactions. ROS need to be detoxified to avoid deleterious reactions, but at the same time, the increased formation of ROS can also be exploited for redox signaling. Glutathione, as the most abundant low-molecular weight thiol in the cellular redox system, is used for both detoxification of ROS and transmission of redox signals. Detoxification of H2O2 through the glutathione-ascorbate cycle leads to a transient change in the degree of oxidation of the cellular glutathione pool, and thus a change in the glutathione redox potential. The shift in the glutathione redox potential can be sensed by glutaredoxins (GRXs), small ubiquitous oxidoreductases, which reversibly transfer electrons between the glutathione redox buffer and thiol groups of target proteins. While very little is known about native GRX target proteins and their behavior in vivo, it is shown here that reduction-oxidation-sensitive GFP (roGFP), when expressed in plants, is an artificial target protein of GRXs. The specific interaction of roGFP with GRX results in continuous formation and release of the roGFP disulfide bridge depending on the actual redox potential of the cellular glutathione buffer. Ratiometric analysis of redox-dependent fluorescence allows dynamic imaging of the glutathione redox potential. It was hypothesized that a similar equilibration occurs between the glutathione buffer and native target proteins of GRXs. As a consequence, even minor deviations in the glutathione redox potential due to either depletion of reduced glutathione (GSH) or increasing oxidation can be exploited for fine tuning the activity of target proteins. The integration of the glutathione buffer with redox-active target proteins is a local reaction in specific subcellular compartments. This observation emphasizes the importance of subcellular compartmentalization in understanding the biology of the cellular redox system in plants.